Interleukin-33 stimulates GM-CSF and M-CSF production by human endothelial cells - Montanari, Eliana; Stojkovic, Stefan; Kaun, Christoph; Lemberger, Christof E.; de Martin, Rainer; Rauscher, Sabine; Gröger, Marion; Maurer, Gerald; Neumayer, Christoph; Huk, Ihor; Huber, Kurt; Demyanets, Svitlana; Wojta, Johann (Thrombosis and Haemostasis, 2016)
Interleukin (IL)-33, a member of the IL-1 family of cytokines, is involved in various inflammatory conditions targeting amongst other cells the endothelium. Besides regulating the maturation and functions of myeloid cells, granulocyte macrophage-colony stimulating factor (GM-CSF) and macrophage-CSF (M-CSF) have been shown to play a role in such pathologies too. It was the aim of our study to investigate a possible influence of IL-33 on GM-CSF and M–CSF production by human endothelial cells. IL-33, but not IL-18 or IL-37, stimulated GM-CSF and M-CSF mRNA expression and protein production by human umbilical vein endothelial cells (HUVECs) and human coronary artery ECs (HCAECs) through the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway in an IL–1-independent way. This effect was inhibited by the soluble form of ST2 (sST2), which is known to act as a decoy receptor for IL-33. The 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase inhibitor fluvastatin could also be shown to moderately reduce the IL-33-mediated effect on M-CSF, but not on GM-CSF expression. In addition, IL–33, IL-1β, GM-CSF and M-CSF were detected in endothelial cells of human carotid atherosclerotic plaques using immunofluorescence. Upregulation of GM-CSF and M–CSF production by human endothelial cells, an effect that appears to be mediated by NF–κB and to be independent of IL-1, may be an additional mechanism through which IL-33 contributes to inflammatory activation of the vessel wall.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Interleukin-33; ST2; endothelial cells; M-CSF; GM-CSF